Effect of Balance on Development Level the Locomotor Capabilities of PAUD Students Padang Pariaman Regency - Bakhtiar, Syahrial; Khairuddin, Khairuddin; Oktarifaldi, Oktarifaldi; Syahputra, Risky; Putri, Lucy Pratama; Asnaldi, Arie (Educatio, 2020)
Based on observations made, the problem in this study is the still low level of development of children's basic motion, especially locomotor abilities. Many factors are thought to be the cause of the low locomotor motion development, one of the dominant causes is the balance of the child. This study aims to look at the effect of balance on the level of development of children's locomotor abilities. The population in this study were all PAUD students in Padang Pariaman District, the random sampling technique was 42 children. The instrument used to obtain data on the balance of PAUD students is MABC 2 sub-test, which is balance, while the locomotor ability of children is obtained through the Test of Gross Motor Development-2 (TGMD-2). Based on the results of research conducted there is an influence of balance on the level of development of the locomotor ability of a child with a rcount value of 0.441> rtable of 0.304 and a significant value (Sig) of 0.003 smaller than the probability of 0.05. The results of this study indicate that the level of locomotor ability development in Padang Pariaman PAUD students is influenced by the balance they have